The role of political theory lecturers in protecting the party's ideological foundation - Đặng Thị Phương Duyên (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
The ideological foundation is the core issue of a revolutionary political party and also the main of the struggle in the ideological field. The duty of safeguarding the Party's ideological foundation falls mostly on ideological workers, particularly political theory teachers. The article examines the contemporary need to battle to protect the Party's intellectual core, highlighting the function of political theory lecturers as well as the implementation constraints placed on this team the job of protecting the Party's ideological foundation.